Static structure of a group of trivalent molten salts: An alternative rigid ion model potential - Yilmaz, M; Gürbüz, H; Kavanoz, HB; Tasseven, Ç; Silbert, M (DE GRUYTER POLAND SP Z O O, 2001)
The total structure factors of eleven 3:1 molten salts and the partial structure factors of molten YCl3 have been calculated using rigid ion model potentials with the functional form originally proposed by Vashishta and Rahman (VR) /18/. The calculations were performed by solving numerically the hypernetted chain approximate theory of liquids. The results of these calculations were compared with neutron diffraction data and those obtained by using the rigid ion potentials proposed by Tatlipinar et al. /16/ (TAPT). The results obtained by using the VR potentials follow the main features of the experimental total structure factors better than those obtained using the TAPT potentials.
Keywords: ALCL3; Materials Science